Unexpected Tension Pneumothorax-Hemothorax during Induction of General Anaesthesia - Ekaterini Amaniti; Chrysoula Provitsaki; Panagiota Papakonstantinou; George Tagarakis; Konstantinos Sapalidis; Ioannis Dalakakis; Dimitrios Gkinas; Vasilios Grosomanidis (Case Reports in Anesthesiology)
Tension pneumothorax during general anaesthesia is a rare but possibly deleterious event, especially where predisposing factors are absent or unknown, making diagnosis even challenging. We describe a case of a healthy middle-aged woman, who was planned to receive general anaesthesia for total thyroidectomy. After intubation, the patient experienced marked hypoxemia (SpO2=75%), hypotension, and tachycardia. Manual positive pressure ventilation seemed to worsen hypoxemia and tachycardia, while apnoeic oxygenation through circle system with valve open slightly improved cardiorespiratory collapse. The effect of positive ventilation, along with the absence of breath sounds in the right hemithorax and cardiorespiratory collapse, established the diagnosis of tension pneumothorax, managed immediately with emergency thoracentesis and placement of a thoracostomy tube. The patient was improved and pneumothorax was confirmed with chest X-ray and CT. The latter also confirmed the presence of bilateral multiple bullae. The operation was postponed and the patient was extubated a few hours later, in good condition. After thorough evaluation for any systemic disease, which was negative, the patient underwent two-stage thoracotomy for bullectomy.